Личный убийца: [роман] / О. И. Приходько - Приходько Олег Игоревич (Черная кошка, 1998)
Экземпляры: К.Х. (20201012) / Инвентарный номер: 38418 / Цена: 48.00 / Авт.знак: П 77 / ГРНТИ: 17.82 / ББК: 84 (2Рос=Рус)6